Stimulation of glutamate receptor protein synthesis and membrane insertion within isolated neuronal dendrites - Kacharmina, Janet Estee (The National Academy of Sciences, 2000)
The selective subcellular localization of mRNAs to dendrites and the recent demonstration of local protein synthesis have highlighted the potential role of postsynaptic sites in modulation of cell–cell communication. We show that epitope-tagged subunit 2 of the ionotopic glutamate receptor, GluR2, mRNA transfected into isolated hippocampal neuronal dendrites is translated in response to pharmacologic stimulation. Further, confocal imaging of N-terminally labeled GluR2 reveals that the newly synthesized GluR2 protein can integrate into the dendritic membrane with the N terminus externally localized. These data demonstrate that integral membrane proteins can be synthesized in dendrites and can locally integrate into the cell membrane.